Uji Aktivitas Antibakteri Sediaan Lulur Ekstrak Etanol Kunyit Terhadap Bakteri Staphylococcus Aureus ATCC 25923 - Riza Aulia Ratna Dela; Diyah Tri Utami (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
Staphylococcus aureus is a normal skin flora that can cause several skin diseases such as ulcers, acne, pneumonia, meningitis, and arthritis. Turmeric contains curcumin which has antibacterial activity. The addition of turmeric extract to the scrub formula can inhibit the activity of S. aureus. The purpose of this study was to determine the effect of turmeric ethanol extract scrub preparations against S. aureus. The research was conducted experimentally in the laboratory. The extraction process is carried out by soxhletation. Antibacterial activity test was carried out using the scrub well method with various formulas of 1%; 3%; 5%, positive control, and negative control. The results showed that formula 3 with a concentration of 5% turmeric ethanol extract showed the highest antibacterial activity against S. aureus with an inhibition zone of 10.9 mm.